2007
DOI: 10.1111/j.1654-1103.2007.tb02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ecological features of species in spatial pattern analysis of a plant community

Abstract: Objective: This empirical study was designed to explore the role of ecological features of species in the spatial patterning of a grassland community. Location: Banks of the river Rhône in France. Material and Methods: First, we explored the spatial pattern of 29 species recorded in the community using spatial autocorrelation analysis of species cover values. Second, we then explored the relationship between the patterns found and a set of life attributes that characterized the ecological features of specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Even on a relatively narrow spatial scale (grain size varying from 1 cm to 7.5 cm) we observed differences in tiller clumping between species, similarly to Purves and Law (2002). Therefore, our results confirmed the importance of clonal growth as a biological source of spatial heterogeneity in plant communities (Herben and Hara 2003) at multiple spatial scales (Wildová 2004;Pottier et al 2007).…”
Section: Scale Dependencysupporting
confidence: 89%
See 1 more Smart Citation
“…Even on a relatively narrow spatial scale (grain size varying from 1 cm to 7.5 cm) we observed differences in tiller clumping between species, similarly to Purves and Law (2002). Therefore, our results confirmed the importance of clonal growth as a biological source of spatial heterogeneity in plant communities (Herben and Hara 2003) at multiple spatial scales (Wildová 2004;Pottier et al 2007).…”
Section: Scale Dependencysupporting
confidence: 89%
“…Likewise, clonal species have been shown to be responsible for long-term space pre-emption and form dominant patches in plant communities (Lovett Doust 1981;Herben 1992). In a previous study, Pottier et al (2007) showed in that same stand community that the competitive abilities of species and their investment in vegetative reproductionthrough clonal growth with long spacers -were associated with the formation of such large and dense patches. The present study focused on the small-scale spatial patterning of tillers inside these patches in relation to a finer measurement of clonal morphology traits.…”
Section: Scale Dependencymentioning
confidence: 97%
“…This suggests that grazing altered the spatial spread of species rather than their intraspecific aggregation. The larger patch size in ungrazed plots compared to grazed ones was possibly due to clonal growth, because fine scale spatial extension of species can be strongly related to clonality in species-rich grasslands (Herben et al 1995;Pottier et al 2007). Grazing, through trampling and defoliation, could have strongly limited the extension of clones by decreasing the number and length of internodes between ramets (Moen et al 1999;Amiaud et al 2008).…”
Section: Spatial Patterns Of Species and Plant Traitsmentioning
confidence: 99%
“…The primary causes of within-community plant spatial patterns can be both biotic and abiotic processes. Spatially limited dispersal of species (Herben et al 2000;Pottier et al 2007), competitive interactions (Tilman 1994;Stoll & Bergius 2005) and soil resource heterogeneity (Burgman 1987) are some of the main processes that shape spatial patterns of plants by influencing intra-specific spatial aggregation. In return, such patterns of species aggregation can modify the relative importance of intra-versus inter-specific competition and influence local species co-existence (Pacala & Levin 1997;Stoll & Prati 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This may cause the formation of a patchy litter layer as frequently found in natural systems (Facelli & Pickett 1991) and create patterns that reflect the clustered spatial structure of the donor populations (cf. Pottier et al 2007). We assume that plant material transfer mimics the availability of seeds and regeneration niches (sensu Grubb 1977) of natural plant communities and fosters pattern formation.…”
Section: Introductionmentioning
confidence: 99%